Pengaruh Kepercayaan, Harga Kamar dan Promosi Digital Terhadap Keputusan Menginap di Hotel 89 Kota Batam - Herman, Hendri; Wahyuni, Dewi; Djuanda, Mochamad; Fitriyani, Leli (eScience Humanity Journal, 2024)
This research was conducted with the aim to determine the influence of trust, room rates and digital promotions on the decision to stay at 89 Batam hotels. The object of this study is 89 hotel consumers in Batam. The total population in this study was 2,413 consumers. The calculation of the number of samples is calculated using the slovin formula. The calculation of the number of samples is calculated using the slovin formula. So that the number of samples was obtained as many as 96 respondents. The sampling technique is by probability sampling. Data collection was carried out by distributing questionnaires to respondents. The collected data is processed using SPSS data processing software. From the results of the study, it is known that partially, trust has a significant effect on the decision to stay, room price has a significant effect on the decision to stay and digital promotion has a significant effect on the decision to stay. It is simultaneously known that trustworthiness, room rates and digital promotions significantly influence stay decisions. An adjusted R square value of 0.459 or 45.9%, which means trustworthiness, room rates and digital promotions can influence stay decisions by 45.9%. While the remaining 54.1% was influenced by other factors not described in this research model